Stroke in young secondary to infective endocarditis complicating hypertrophic cardiomyopathy – A case report - Bhandari, Abhishek; Shah, Bhupendra; Mahaseth, Aditya; Sharma, Sanjib Kumar (Nepalese Heart Journal, 2019)
Hypertrophic cardiomyopathy is an autosomal dominant disease of cardiac sarcomere with the varied clinical presentation. The common manifestations are heart failure (dyspnea), palpitations, chest pain, stroke and even sudden death. Majority of patients are not recognized because of being asymptomatic. Stroke is one of the complications of hypertrophic cardiomyopathy and usually occurs in the setting of atrial fibrillation, advanced age and congestive cardiac failure. Although infective endocarditis is known, but relatively uncommon, complication of hypertrophic cardiomyopathy, it is not reported from Nepal. We report here a case of 42-year male patient with hypertrophic cardiomyopathy in normal sinus rhythm with infective endocarditis who developed malignant cardioembolic stroke involving left middle cerebral artery territory.